Relationship between Red Blood Cell Distribution Width (RDW), Bilirubin, and Clinical Characteristics of Patients with Gastric Cancer - قدار, تغريد; عبدالله, نادر; سلهب, ايمان (Latakia University Journal -Medical Sciences Series, 2020)
Objective: The purpose of the present study was to investigate whether a relationship exists between bilirubin, RDW, and prognostic factors for gastric cancer (tumor stage - tumor markers). Methods: The study included 112 individuals admitted to Tishreen University Hospital and the Oncology Center in Latakia during the period between July 2018 and December 2019. They were distributed into two groups as follow: the group of gastric cancer patients included 56 patients (33 males and 23 females) between the ages of 37 and 83 years, and the control group included 56 individuals (34 males and 22 females) between the ages of 37 and 80 years. The stage of gastric cancer was evaluated based on the AJCC (American Joint Committee on Cancer) cancer staging system. Patients were interrogated, and social and behavioral information were obtained, then venous blood samples were obtained for biomedical evaluation. Statistical analysis was done using SPSS version 25 software. Results: Bilirubin and RDW were significantly associated with the prognostic factors of gastric cancer. RDW was positively associated with the tumor stage and tumor markers (CEA and CA19-9). Total bilirubin (TBIL) and indirect bilirubin (IBIL) were negatively associated with these factors, while direct bilirubin (DBIL) showed no significant association. Patients with gastric cancer had higher RDW than healthy controls, while total bilirubin (TBIL) and indirect bilirubin (IBIL) were significantly decreased. The results of our study indicate that both RDW and bilirubin could be potential prognostic factor for gastric cancer.